Evaluation of Enteral Nutrition in Newborn Intubated with Cuffed and Uncuffed Tube. - Yuksel, Buse Duygu; Dogan, Aysel Kokcu (International Journal of Caring Sciences)
Purpose: This study was designed in the descriptive and relational screening model for the evaluation of enteral nutrition in the care of newborns treated with cuffed or uncuffed intubation tube and was conducted between March 2018 and June 2019. Design and Methods: The sample of the research consisted of 129 newborn babies intubated with 47 cuffed and 82 uncuffed tubes in the Cardiovascular Surgery Intensive Care and Neonatal Intensive Care Units in a private University Hospital in Istanbul and whose parents volunteered to participate in the study. Data was collected using the "Information Form" and the "Evaluation of Enteral Nutrition Data Collection Form in the Care of Newborns treated with Cuffed and Uncuffed Intubation Tube." It has been determined that feeding is more effective in babies using cuffed intubation tubes in relation to the nutrition given to all babies in which both intubation tubes are applied. Results: After full 24 hours of feeding; between the nutritional status and the feeding probe and the presence of gas in the stomach; between newborn weight and abdomen examination and skin color; between birth week and SpO2% values and sedation status of the baby; it was found that there was a significant difference (p<0.05) statistically, between the intubation tube applied to infants and the level of tube, cuff pressure, fixation band, defecation, gastric residue, oral secretion and intraoral secretion after feeding. Conclusion: It was determined that enteral feeding was effective in the care of newborns treated with cuffed and uncuffed intubation, and the growth and development of babies with cuffed tubes were positively affected compared to those with uncuffed tubes. Therefore, based on these results, it is advised that the quality of care in the development of intubated newborn babies shall be improved by ensuring the continuity of in-service training programs for the nurses.